Optimization of building-integrated photovoltaic thermal air system combined with thermal storage - Xiang, Yetao; Gan, Guohui (Oxford University Press, 2015)
Photovoltaic (PV) combined with phase change material (PV/PCM) system is a hybrid solar system that uses a PCM to reduce the PV temperature and to store energy for other applications. This study aims to increase the integrated PV efficiency of buildings by incorporating PCM while utilizing the stored heat in PCM for controlling indoor conditions. Experiments have been carried out on a prototype PV/PCM air system using monocrystalline PV modules. Transient simulations of the system performance have also been performed using a commercial computational fluid dynamics package based on the finite volume method. The results from simulation were validated by comparing it with experimental results. The results indicate that PCM is effective in limiting temperature rise in PV device and the heat from PCM can enhance night ventilation and decrease the building energy consumption to achieve indoor thermal comfort for certain periods of time.